The Last Words of EHRC to Turkish Government: “Recognize the Alevis Officially” (Journal of Alevism-Bektashism Studies, 2017)
Alevi faith is a belief with particular features which distinguished it in many respects from the Sunni understanding of İslam. Alevis are the second largest religious community and it is estimated that there are at least 15 million followers of the Alevi faith in Turkey. Despite the secular nature of the Republic of Turkey, İslamic religious service is regarded as a public service in Turkey. But, Alevis cannot benefit from these services. Public service that exclusively to Sunni Muslim is incompatible with the constitutional principles of secularism and neutrality of public services. In addition, Alevis have many problems such as formation of Religious Affairs Department (RAD), compulsory religious education, demand of recognition for their places of worship, namely the cemevis. They want their State to allocate budget for practice of the Alevi faith; recruit Alevi religious leaders as civil servants; grant the Alevi places of worship (cemevis) to the status of places of worship. Main aim of this article is analize to the European Court of Human Rights’s cases (ECHR) about Alevis’ problems within the context of the right to freedom of conscience and religion and its conclusions.